PEMBUATAN SIRUP SALAK PADANG SIDIMPUAN DENGAN PENAMBAHAN EKSTRAK KELOPAK BUNGA ROSELLA - Zulfadli, Muhammad; Pato, Usman; Hamzah, Faizah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Syrup is one of the liguid processed products consumed by some people as a thirst releasing drink. The purpose of this research was to get the best formulation of padang sidimpuan salacca syrup with the addition of rosella flower petal extract that meet the SNI 01-3455-2013. Study was conducted experimentally using Completely Randomized Design with five treatments and four replications thus obtained 20 experimental units. The treatments in this study K0 (salacca extract 100% : rosella flower petal extact 0%), K1 (salacca extract 95% : rosella flower petal extact 5%), K2 (salacca extract 90% : rosella flower petal extact 10%), K3 (salacca extract 85% : rosella flower petal extact 15%), and K4 (salacca extract 80% : rosella flower petal extact 20%). The data obtained were analyzed by statistic using Analysis of Variance (ANOVA) followed by Duncan’s New Multiple Range Test (DNMRT) on 5% level. The result showed that ratio of salacca extract test rosella flower petal extract to making syrup significantly affected the degree of acidity (pH), sucrose, viscosity, total dissolved solid and sensory. The best treatment was K2 with pH 4.55, sucrose 69.75%, viscosity 346.64cP, total dissolved solid 69.90°brix. Syrup characteristic of treatment K2 in descriptive test had a purplish red color, scented salacca flavor, sweet little acid taste, viscous consistency, and overall assessment were liked by the panelists. Keywords: Syrup, Salacca, Rosella flower petal extract